Association between C reactive protein and microvascular and macrovascular dysfunction in sub-Saharan Africans with and without diabetes: the RODAM study - Hayfron-Benjamin, Charles F.; Zee, Anke H. Maitland-van der; Born, Bert-Jan van den; Amoah, Albert G. B.; Meeks, Karlijn A. C.; Klipstein-Grobusch, Kerstin; Schulze, Matthias B.; Spranger, Joachim; Danquah, Ina; Smeeth, Liam; Beune, Erik J. A. J.; Mockenhaupt, Frank; et al. (BMJ Open Diabetes Research & Care, 2020)
Introduction Although inflammation assessed by elevated C reactive protein (CRP) concentration is known to be associated with risk of cardiovascular disease, its association with microvascular and macrovascular dysfunction in diabetes and non-diabetes remains unclear. We examined the association between CRP and diabetes and associated microvascular and macrovascular dysfunction in sub-Saharan Africans with and without diabetes. - Research design and methods Cross-sectional analyses of baseline data from the multicenter RODAM study (Research on Obesity and Diabetes among African Migrants) including 5248 Ghanaians (583 with diabetes, 4665 without diabetes) aged 25-70 years were done. Logistic regression analyses were used to examine the associations between CRP Z-scores and diabetes and microvascular (nephropathy) and macrovascular (peripheral artery disease (PAD)) dysfunction, with adjustments for age, sex, site of residence, smoking, body mass index, systolic blood pressure, and low-density lipoprotein cholesterol. - Results In the fully adjusted models, higher CRP concentration was significantly associated with diabetes (adjusted OR 1.13; 95% CI 1.05 to 1.21, p=0.002). In participants with diabetes, higher CRP concentration was associated with PAD (1.19; 1.03 to 1.41, p=0.046) but not nephropathy (1.13; 0.97 to 1.31, p=0.120). Among participants without diabetes, higher CRP concentration was associated with higher odds of PAD (1.10; 1.01 to 1.21, p=0.029) and nephropathy (1.12; 1.04 to 1.22, p=0.004). - Conclusions In this study, higher CRP concentration was associated with higher odds of diabetes in sub-Saharan Africans. Also, higher CRP concentration was associated with higher odds of nephropathy and PAD in non-diabetes and higher odds of PAD in diabetes. CRP may be an important marker for assessment of risk of diabetes and risk for PAD and nephropathy in sub-Saharan Africans with and without diabetes.
Gesehen am 30.10.2020